Vaginal Epithelium Transiently Harbours HIV-1 Facilitating Transmission - Prabhu, Varsha M.; Padwal, Varsha; Velhal, Shilpa; Salwe, Sukeshani; Nagar, Vidya; Patil, Priya; Bandivdekar, Atmaram H.; Patel, Vainav (Frontiers in Cellular and Infection Microbiology, 2021)
Vaginal transmission accounts for majority of newly acquired HIV infections worldwide. Initial events that transpire post-viral binding to vaginal epithelium leading to productive infection in the female reproductive tract are not well elucidated. Here, we examined the interaction of HIV-1 with vaginal epithelial cells (VEC) using Vk2/E6E7, an established cell line exhibiting an HIV-binding receptor phenotype (CD4-CCR5-CD206+) similar to primary cells. We observed rapid viral sequestration, as a metabolically active process that was dose-dependent. Sequestered virus demonstrated monophasic decay after 6 hours with a half-life of 22.435 hours, though residual virus was detectable 48' hours post-exposure. Viral uptake was not followed by successful reverse transcription and thus productive infection in VEC unlike activated PBMCs. Intraepithelial virus was infectious as evidenced by infection in trans of PHA-p stimulated PBMCs on co-culture. Trans-infection efficiency, however, deteriorated with time, concordant with viral retention kinetics, as peak levels of sequestered virus coincided with maximum viral output of co-cultivated PBMCs. Further, blocking lymphocyte receptor function-associated antigen 1 (LFA-1) expressed on PBMCs significantly inhibited trans-infection suggesting that cell-to-cell spread of HIV from epithelium to target cells was LFA-1 mediated. In addition to stimulated PBMCs, we also demonstrated infection in trans of FACS sorted CD4+ T lymphocyte subsets expressing co-receptors CCR5 & CXCR4. These included, for the first time, potentially gut homing CD4+ T cell subsets co-expressing integrin ɑ4β7 and CCR5. Our study thus delineates a hitherto unexplored role for the vaginal epithelium as a transient viral reservoir enabling infection of susceptible cell types.